A novel regulatory pathway in granulosa cells, the LH/human chorionic gonadotropin‐microRNA‐125a‐3p‐Fyn pathway, is required for ovulation. Issue 8 (28th April 2015) - Grossman, Hadas; Chuderland, Dana; Ninio‐Many, Lihi; Hasky, Noa; Kaplan‐Kraicer, Ruth; Shalgi, Ruth
Abstract : Granulosa cells support the developing oocytes and serve as transducers of the ovulatory stimulus induced by LH surge. Fyn kinase is expressed in granulosa cells, though its role in these cells has not been studied. In human embryonic kidney 293T cells, microRNA (miR)‐125a‐3p down‐regulates Fyn expression, causing a decrease in cells' migratory ability. Our aim was to explore the role of miR‐125a‐3p and Fyn in granulosa cells toward ovulation, focusing on migration as a possible mechanism. We demonstrate expression of miR‐125a‐3p and Fyn in mouse mural granulosa cells of preovulatory follicles and miR‐125a‐3p‐induced down‐regulation of Fyn expression in a granulosa cell line (rat). Administration of human chorionic gonadotropin (hCG; LH analog) caused a 75% decrease in the in vivo miR‐125a‐3p:Fyn mRNA ratio, followed by a 2‐fold increased migratory ability of mural granulosa cells. In the hCG‐treated granulosa cell line, miR‐125a‐3p expression was decreased, followed by Fyn up‐regulation and phosphorylation of focal adhesion kinase and paxillin, enabling cell migration. An in vivo interference with miR‐125a‐3p:Fyn mRNA ratio in granulosa cells by intrabursal injections of Fyn small interfering RNA or miR‐125a‐3p mimic caused a 33 or 55% decrease in the number of ovulated oocytes, respectively. These observations reveal a new regulatory pathway in mural granulosa cells under the regulation of LH/hCG. Modulation of cell migration may account for the significance of the LH/hCG‐miR‐125a‐3p‐Fyn pathway to ovulation.—Grossman, H., Chuderland, D., Ninio‐Many, L., Hasky, N., Kaplan‐Kraicer, R., Shalgi, R. A novel regulatory pathway in granulosa cells, the LH/human chorionic gonadotropin‐microRNA‐125a‐3p‐Fyn pathway, is required for ovulation. FASEB J. 29, 3206‐3216 (2015). www.fasebj.org